Magnus Lindberg: Narratives of Time and Space. - Howell, Tim (Contemporary Music Review, 2014)
The creative energy which has emerged from Finland over the past 25 years or so has generated a great deal of interest, not just in terms of scholarship but amongst the concert-going public at large. Magnus Lindberg is a leading, internationally renowned figure in contemporary music and his preoccupation with matters of musical timescale—and its relationship to his native homeland—forms the basis of this article. An analytical case study of his recent orchestral workEragives a focus to more wide-ranging discussions of time, space, motion and continuity, while helping us to understand the broad appeal of this undoubtedly modern music to a refreshingly wide-ranging audience.